Towards an innovative digital transformation of public administration in Romania through the implementation of artificial intelligence in the process of developing public policies in the field of health - Golea, Daniela Georgiana; Radu, Andreea Florina; Coșa, Oana Ștefania (Technium Social Sciences Journal, 2025)
In the context of global digitisation and the increasing complexity of public health challenges, the integration of artificial intelligence (AI) into public administration emerges as a transformative strategy. This article explores the potential of AI to fundamentally reshape the process of policy-making in Romania's healthcare sector, aiming to transition from reactive governance to anticipatory and data-driven decision-making. The study begins by outlining the conceptual framework of digital transformation and algorithmic governance, followed by an analysis of current limitations in Romania's public health administration. By examining international best practices and identifying contextual opportunities, the paper proposes a structured model for AI integration, tailored to Romania's institutional landscape. The originality of this study lies in its interdisciplinary approach, combining digital innovation theory with empirical public policy analysis to support a paradigm shift in governance.